(B+2)(b-3)=-6 solve for b

## Solve for b

Tutors, please sign in to answer this question.

# 2 Answers

Hi Lila;

(B+2)(b-3)=-6

I am assuming that B and b are the same and this is just a typographical error.

(b+2)(b-3)=-6

Let's FOIL...

FIRST...(b)(b)=b

^{2}OUTER...(b)(-3)=-3b

INNER...(2)(b)=2b

LAST...(2)(-3)=-6

b

^{2}-3b+2b-6=-6b

^{2}-b-6=-6Let's add 6 to both sides...

b

^{2}-b-6+6=-6+6b

^{2}-b=0b(b-1)=0

**b=0, and/or**(b-1)=0

**, b=1.**

Let's check our work...

b=0

(b+2)(b-3)=-6

(0+2)(0-3)=-6

(2)(-3)=-6

-6=-6

b=1

(1+2)(1-3)=-6

(3)(-2)=-6

-6=-6

is the B different than b or are those the same variable. if they are then you would expand the equation to b^2 + b -6 = -6 then solve for b which would give you 0 and 1. if they are not the same then you would need to move things around and get -6/(B+2)
+ 3= b.